Purification of Crude Glycerol from Biodiesel By-product by Adsorption using Bentonite - Erniati Anzar; M. Syahirman Yusi; Yohandri Bow (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The production of glycerol from biodiesel by-product that was obtained from waste cooking oil has low purity. This crude glycerol contains impurities such as methanol, catalyst, soap and water. Analysis result shows that crude glycerol contains 67.7% water, 16.7% ash with density 1.1217 g/mL. The impurities were able to be adsorbed using bentonite which was activated in sulphuric acids 1.5 M and characterized by SEM-EDX. The purified glycerol after being treated with bentonite at 60 C for 75 minutes was fulfilled The SNI 06-1564-1995 requirement i.e. 89.5% glycerol, 4.3% water, 3.6% ash and density 1.2212 g/mL. From the experiment can be concluded the activated bentonite showed a capacity in adsorbing and removing impurities in waste cooking oil.